A Comparative Study: Degradation of 2, 5-Dichlorophenol in Wastewater and Distilled Water by Ozone and Ozone-UV. (3rd May 2016) - Alexander, Jacqueline C.; Ramírez-Cortina, Clementina R.
ABSTRACT: The effectiveness of ozone and ozone-UV processes on effluents containing chlorophenol was evaluated. Experiments were performed using 3.06 mM of 2, 5-dichlorophenol in distilled water and wastewater at pH 7 with ozone dose of 37 mg/L. An ozone dose of 1.2 g/h was effective in completely degrading 2, 5-dichlorophenol and reducing the toxicity of its by-products. Overall, ozone-UV process was more effective in the oxidation of 2, 5-DCP. Ozone-UV treatment of wastewater showed the highest mineralization (53%), dechlorination (100%), COD removal (75%), and biodegradability (BOD5 /COD = 0.85). The organic/inorganic matters in wastewater seem to have a positive effect on the oxidation of 2, 5-DCP and supports the use of ozone and ozone-UV processes for industrial effluent treatment.